Potential Role and Prognostic Value of Erythropoietin Levels in Patients With Severe Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement - Mas-Peiro, Silvia; Seppelt, Philipp C.; De Rosa, Roberta; Murray, Marie-Isabel; Yogarajah, Jörg; Berkowitsch, Alexander; Fichtlscherer, Stephan; Zeiher, Andreas M.; Vasa-Nicotera, Mariuca (Frontiers in Cardiovascular Medicine, 2020)
Background Both EPO levels and anemia have shown prognostic value in several cardiac disorders. An observational study with a prospective follow-up was performed to investigate their independent prognostic roles in severe aortic stenosis. Methods An up to 36-month follow-up of consecutive patients with severe aortic stenosis undergoing TAVR in a high-volume center was performed. Patients with eGRF <30 mL/min/1.73m2 were excluded. EPO levels and/or anemia status and its association with mid-term mortality were assessed. Results Out of 407, 360 met eligibility criteria. Median age was 83 years, with 71.4% having a NYHA class III/IV. Anemia was present in 51.9%, and iron deficiency in 52.8%. Median (IQR) EPO levels were 14.4 (9.30-24.30) mIU/mL. Median follow-up was 566 days. Anemia was associated with overall mortality (HR 2.40, 95%CI 1.51-3.80, p<0.001). Higher logEPO levels were associated with mid-term mortality (HR 4.05, 95%CI 2.29-7.16, p<0.001), even after adjusting for clinically and/or statistically relevant factors (multivariate HR 2.25, 95 CI 1.09-4.66, p=0.029). Kaplan-Meier analyses showed early diverging curves for anemia vs non-anemia, whereas curves for patients in various EPO level quartiles started to diverge at about 100 days, with differences consistently increasing during the subsequent entire follow-up period. Conclusions Differently from anemia, which was a strong predictor for both early and late mortality in severe aortic stenosis after TAVR, independent prognostic value of EPO only emerged after post-TAVR recovery. EPO prognostic value was independent from anemia and mild-to-moderate renal dysfunction. High EPO levels could be useful to identify patients with severe aortic stenosis showing a compromised mid-term survival in spite of TAVR use and independently from early TAVR results.